Bakawugh Tradition In Nagari Sumpur Kudus Sijnjung District West Sumatera Province - Hasnah Anita Putri, Hasnah Anita Putri; Febri Yulika; Mutia Kahanna (Kirana Publisher (KNPub), 2023)
This thesis entitled “Bakawugh Tradition in Nagari Sumpur Kudus Sijunjung west Sumatera Province” The purpose of this research is to regency describes the bakawugh tradision carried out by the community in Nagari Sumpur Kudus. The theory used in this thesis is symbolic interpretative theory by Clifford Geertz. The medhod used by the author is qualitativemethod, with data collection techniques namely observation, interview, and dokumentation. The results of the study show that the background of the bakawugh tradition comes from the idea of Syekh Ibrahim himself in 1520. In general, the meaning of the bakawugh tradition is thanksgiving, gathering and practicing the charakteristics of Syekh Ibrahim. Social, respect of mind, patience and struggle, togetherness, and hope. Furthermore there are meanings in the contents of jambaigh such as the meaning of peace, purity, freedom, simplicity and ease, unity, tenderness, kinship and closeness, closeness, brotherhood.